Self-criticism and romantic relationship satisfaction as serial mediators of links between childhood psychological maltreatment and loneliness - Birni, Gaye; Satici, Seydi Ahmet; Deniz, M. Engin (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Background: Psychological maltreatment may be one of the causes of adults' loneliness despite having a partner. There are some links between psychological maltreatment, self-criticism, relationship satisfaction, and loneliness in the literature. But the nature of these links requires further explanation.Objective: The present study examined the serial mediation role of self-criticism and romantic relationship satisfaction on the pathway from childhood psychological maltreatment to loneli-ness, in a Turkish sample. Participants and settings: In total 403 individuals (Female = 294, Male = 109) participated from 53 different cities in Turkiye. Participants were either dating (65.8 %), had a fiance ' e (4 %), or were married (30.3 %).Method: The data was collected using Psychological Maltreatment Questionnaire, UCLA Loneli-ness Scale, Self-criticism Rumination Scale, and the Relationship Assessment Scale.Results: Structural equation modeling results indicated that self-criticism and romantic relation-ship satisfaction fully mediated the impact of psychological maltreatment on loneliness. The model was a good fit [chi 2 (29, N = 403) = 63.846, p < .001; chi 2/df = 2.20; SRMR = 0.061; RMSEA = 0.055; GFI = 0.969; CFI = 0.979; NFI = 0.963; IFI = 0.979].Conclusions: Childhood experiences of psychological maltreatment can continue to haunt in-dividuals, even as adults. Although being in a relationship can help individuals with their lone-liness, psychologically maltreated adults may feel lonely in their relationships due to self-criticism and dissatisfaction. Interventions focused on childhood psychological maltreatment and self-criticism may help lonely adults. Along with this focus, relationship satisfaction can be addressed in family/couple counseling.
Keywords: Psychological maltreatment; Loneliness; Self-criticism; Relationship satisfaction; DEPRESSIVE SYMPTOMS; HEALTH; ADULTS; TIME; Family Studies; Psychology; Social Work